2012
DOI: 10.1097/iae.0b013e31824d09a8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum and Prognosis of Uveal Melanoma Based on Age at Presentation in 8,033 Cases

Abstract: Compared with mid adults and older adults, young patients manifested a higher proportion of iris melanoma. Compared with older adults, young and mid adults showed smaller melanoma basal dimension and lower tumor-related metastasis and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
195
3
27

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 259 publications
(252 citation statements)
references
References 20 publications
8
195
3
27
Order By: Relevance
“…There have been a few studies to assess features and prognosis of uveal melanoma in non-Caucasians. [3][4][5][6][7][8][9][10] Margo et al 5 evaluated enucleated eyes with uveal melanoma in the Florida Cancer Data System between 1981 and 1993, stratified by race, and noted 814 (94%) Caucasians, 47 (5%) Hispanics, and 4 (o1%) African Americans. They observed that Caucasian men had a 72-fold greater risk for uveal melanoma compared to African American men and Caucasian women had 22-fold risk compared with African American women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few studies to assess features and prognosis of uveal melanoma in non-Caucasians. [3][4][5][6][7][8][9][10] Margo et al 5 evaluated enucleated eyes with uveal melanoma in the Florida Cancer Data System between 1981 and 1993, stratified by race, and noted 814 (94%) Caucasians, 47 (5%) Hispanics, and 4 (o1%) African Americans. They observed that Caucasian men had a 72-fold greater risk for uveal melanoma compared to African American men and Caucasian women had 22-fold risk compared with African American women.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] We have previously reviewed our 40-year experience with uveal melanoma in over 8000 patients relative to patient age at presentation, clinical features, tumor size, presence of melanocytosis, and classification. [10][11][12][13] Herein, we explore this large cohort for the prevalence and outcomes of uveal melanoma based on patient race.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor epicenters are usually found in the choroid, but may also arise from the iris and ciliary body. About 45% of uveal melanoma cases were recorded in adults older than 60 years and 53% were in adults ages between 21 and 60 years old (1). The 5-year survival rate of uveal melanoma patients from 1973 to 2008 is 81.6% (2).…”
Section: Introductionmentioning
confidence: 99%
“…The average age of initial diagnosis of uveal melanoma is approximately 60 years [7,12]. Compared with older patients, younger patients are more likely to present with iris melanomas, have associated melanocytosis, and a lower risk of metastatic disease [13]. Pediatric and congenital cases have been reported, but seldom occur [2,14].…”
Section: Epidemiologymentioning
confidence: 99%